Media Pembelajaran Gerak Lurus Beraturan Dan Gerak Lurus Berubah Beraturan Dengan Adobe Flash : Studi Kasus : SMA Veteran Purwokerto - Sri Heneng Prasastono; Mohammad Hidayatul Holili (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Physics is a branch of science that requires more cognitive abilities, while the ability to receive information from each person is different. One effective way to deliver information is to use simulations.This research was conducted at SMA Veteran Purwokerto, research participants were students of class X, a case study that explored a group of students, with the method of observation and literature study. This study aims to find out the increase in students' understanding of concepts that are specifically related to Regular Straight Motion and Straight Changed Irregular Motion through learning media, and to determine student involvement in the learning process. To find out whether or not there was an increase in students 'understanding of the concept of Straight Motion Straight Motion Irregularly Changed, researchers compared students' understanding before and after learning with learning media.The results showed that overall there was an increase in understanding of the concepts of Irregular Straight Motion and Irregularly Changed Straight Motion, overall student involvement was very active.